Challenges in Protecting Victims of Bullying within the Juvenile Criminal Justice System and Efforts to Achieve Substantive Justice for Victims of School Bullying - Muhammad Zainul Arifin; Redi Pirmansyah; M. Iqbal (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2026)
Bullying within the school environment remains a serious issue that significantly affects a child’s psychological and social development. Nevertheless, within the juvenile criminal justice system, legal protection tends to focus more heavily on child offenders than on victims, resulting in inadequate protection and recovery mechanisms for children who experience bullying. This study aims to examine the implementation of legal protection for child victims of bullying within the current juvenile criminal justice framework, as well as to formulate an ideal model of protection capable of achieving substantive justice and supporting victims’ psychological recovery from trauma. The research adopts a normative juridical method through both statutory and conceptual approaches. Primary legal materials include Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, Law Number 35 of 2014 concerning Child Protection, and Law Number 31 of 2014 concerning the Protection of Witnesses and Victims. These are complemented by secondary legal materials derived from relevant academic literature and scholarly works. The findings demonstrate that the existing system has not yet fully accommodated the interests and recovery needs of victims, particularly due to an approach that remains largely offender-oriented within diversion mechanisms and restorative justice practices. This study therefore proposes a victim-centred protection model that integrates legal safeguards with psychological rehabilitation through trauma healing, strengthens the role of victims throughout judicial proceedings, and reinforces institutional mechanisms for victim protection. The academic contribution of this research lies in the development of a more comprehensive framework for victim protection within the juvenile criminal justice system, with particular emphasis on substantive justice and holistic recovery for victim